PILIHAN RASIONAL WANITA SEBAGAI ATLET PANJAT TEBING (STUDI KASUS WANITA YANG TERGABUNG DIDALAM FEDERASI PANJAT TEBING INDONESIA RIAU) - Ahmad Rifandi; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study looks at the rationale of women in choosing a profession as a sportsathlete rock climbing. In this case the researchers set the location of research in theUniversity of Riau campus area which is the center of sporting activities rock climbingRiau province. The object of this study is also related to the response of women tosociety streotipe about women who cultivate rock climbing sport. The subjects of thisstudy were all female athletes who joined in the Federation Climbing Indonesia Riau,which amounted to five (5) people. Data collection techniques used observation andinterview techniques. Then the data were analyzed by using descriptive qualitativeanalysis method. Based on the results of the analysis found that the rational choice ofwomen in the sport of rock climbing is because their orientation to the goal, they havetheir own goals, so that the attention is the goal. So that all kinds of risks andconsequences do not become something that interfere with their mind, the mostimportant is the goal is achieved. The reason they survive is due to intrinsic factors:love, comfort, challenges, and achievement and extrinsic factors: money, and career /employment. Meanwhile, women's response to stereotypes is said to be positive becausethey have a good knowledge of the streotype, and have experienced it themselves, but donot make it as an obstacle and even more obstacles as a motivation more, spirit, and astrong will to develop be better. While the attitudes of the female athlete against anykind of risk that there is likely not to question, because they choose rock climbing sporton the basis of a sense of love and pleasure.Keywords: Gender, Climbing, women